E-005 Normalization of elevated idiopathic intracranial venous pressures after manometry and high-volume lumbar puncture in a patient with pseudotumor cerebri. (4th August 2020) - Brown, M; Wolfe, T
Abstract : Treatment of idiopathic intracranial hypertension (IIH), also known as pseudotumor cerebri, generally prioritizes alleviating headaches and preserving vision. If medical management is unsuccessful, possible surgical treatment options depending on symptom severity include serial lumbar punctures, venous sinus stenting, optic nerve sheath fenestration (ONSF), and cerebrospinal fluid (CSF) shunting. Venous sinus stenting has remained controversial as cerebral vein stenosis may not be a primary cause. In our case, we present a 38-year-old female with known pseudotumor cerebri who underwent a diagnostic cerebral angiogram with manometry and high-volume lumbar puncture. Pre-lumbar puncture manometry demonstrated venous pressures throughout the left and right transverse sinuses and distal superior sagittal sinus ranging from 25–30 mmHg with associated bilateral transverse-sigmoid junction stenoses. The patient was then placed in the lateral decubitus position and a lumber puncture at L2-3 was performed. Opening pressure was measured at 29 cm H2 O, 30 mL of clear CSF was removed, and closing pressure was measured at 8.5 cm H2 O. Post-lumbar puncture manometry demonstrated normalization of respective venous pressures ranging from 8–12 mmHg with resolution of associated bilateral transverse-sigmoid junction stenoses and improved venous sinus calibers. Following the procedure, the patient reported resolution of headache. These results indicate that cerebral venous stenoses in the setting of IIH may be a secondary phenomenon. Thus, patients may benefit from CSF shunting as a primary surgical treatment option. In order to establish treatment efficacy, future studies could evaluate for stenosis and pressure gradient recurrence after CSF shunting. Disclosures: M. Brown: None. T. Wolfe: None.